FOXO1 Overexpression Attenuates Tubulointerstitial Fibrosis and Apoptosis in Diabetic Kidneys by Ameliorating Oxidative Injury via TXNIP-TRX. (6th March 2019) - Ji, Linlin; Wang, Qingzhu; Huang, Fengjuan; An, Tingting; Guo, Feng; Zhao, Yanyan; Liu, Yang; He, Yanyan; Song, Yi; Qin, Guijun
Abstract : Objective . The generation of hyperglycemia-induced reactive oxygen species (ROS) is a key event in diabetic nephropathy (DN) development. Since forkhead box class O1 (FOXO1) is associated with oxidative stress and shows a positive effect on DN, its role on renal function and the underlying mechanism is still unclear. Methods . We examined the role of FOXO1 in vivo (in a transgenic diabetic mouse model overexpressing Foxo1 ) and in vitro (in human HK-2 cells with FOXO1 knockin (KI) and knockout (KO) cultured under high glucose). Results . Renal proximal tubular cells of kidney biopsies from patients with DN showed tubulointerstitial fibrosis and apoptosis. Accordingly, these proximal tubular injuries were accompanied by the increase of ROS generation in diabetic mice. Tissue-specific Foxo1 overexpression in transgenic mice had a protective effect on the renal function and partially reversed tubular injuries by attenuating the diabetes-induced increase in TXNIP and decrease in the TRX levels. FOXO1 knockin and knockout HK-2 cells were constructed to identify the associations between FoxO1 and TXNIP-TRX using CRISPR/CAS9. Similarly, the effects of FOXO1 KI and KO under high glucose were significantly modulated by the treatment of TRX inhibitor PX-12 and TXNIP small interfering RNA. In addition, TXNIP and TXN were identified as the direct FOXO1 transcriptional targets by chromatin immunoprecipitation. Conclusion . The regulatory role of FOXO1/TXNIP-TRX activation in DN can protect against the high glucose-induced renal proximal tubular cell injury by attenuating cellular ROS production. Modulating the FOXO1/TXNIP-TRX pathway may be a new therapeutic target in DN.